2012
DOI: 10.2494/photopolymer.25.385
|View full text |Cite
|
Sign up to set email alerts
|

Low Thermal Expansion Composites Prepared from Polyimide and ZrW<su>2O8 Particles with Negative Thermal Expansion

Abstract: Inorganic/polymer composite films with adjustable small thermal expansion were prepared by incorporating sub-m sized particles of zirconium tungstate (ZrW 2 O 8 ) into aromatic polyimide (PI). ZrW 2 O 8 particles exhibit negative coefficients of thermal expansion (CTE) between 4.8 to 8.7 ppm/K. The cross-sectional SEM images of ZrW 2 O 8 /PI composite films indicate that filler particles are homogeneously dispersed in PI matrix without aggregation. The CTEs of these films are linearly decreased with increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 11 publications
(16 reference statements)
1
18
0
Order By: Relevance
“…However, in some cases, such as Al 2 TiO 5 , microstructural design and microcrack formation can be used to advantage to produce low thermal expansion materials with high thermal shock resistance [10]. On the other hand, the second approach makes use of the addition of thermomiotics, as the dispersed phase, in composites [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. The most common role of thermomiotics in composites is to control the CTE of the matrix phase, which could be a metal, ceramic or polymer.…”
Section: Introductionmentioning
confidence: 99%
“…However, in some cases, such as Al 2 TiO 5 , microstructural design and microcrack formation can be used to advantage to produce low thermal expansion materials with high thermal shock resistance [10]. On the other hand, the second approach makes use of the addition of thermomiotics, as the dispersed phase, in composites [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. The most common role of thermomiotics in composites is to control the CTE of the matrix phase, which could be a metal, ceramic or polymer.…”
Section: Introductionmentioning
confidence: 99%
“…When ZnO NPs was loaded at 1 wt %, 5 wt %, and 10 wt %, the CTE value were reduced to 33.5 ppm/K, 31.3 ppm/K, and 30.1 ppm/K, respectively. Moreover, the TMA thermograms of the ZSQ showed no discernible transitions, which indicated that the nanosized ZnO NPs were well dispersed and the photocuring process complete . In addition, the nanoindentation results of UV‐cured LPMSQ, as well of ZnO composites, were summarized in Figure (B) As shown, both the modulus and hardness values drastically increased with increasing ZnO content.…”
Section: Resultsmentioning
confidence: 93%
“…Moreover, the TMA thermograms of the ZSQ showed no discernible transitions, which indicated that the nanosized ZnO NPs were well dispersed and the photocuring process complete. [35][36][37][38] In addition, the nanoindentation results of UV-cured LPMSQ, as well of ZnO composites, were summarized in Figure 6(B) As shown, both the modulus and hardness values drastically increased with increasing ZnO content. It was noteworthy that the modulus values obtained for ZSQ5 and ZSQ10 were substantially higher than previously studied hybrid materials, with a high modulus of 9.4 GPa.…”
Section: Thermal Properties Of Composite Filmsmentioning
confidence: 99%
“…The investigations introduced in this study are only a few cases. We have also studied slurries and pastes including polymer/ ceramics containing negative thermal expansion hybrid films, 59) porous magnetic filters for O 2 gas concentration, 60) and so on. It is hoped that this research will lead to scientific elucidation of present ceramic processing know-how and result in the development of higher-performance ceramic materials.…”
Section: Discussionmentioning
confidence: 99%